2010
DOI: 10.1177/0018720810375692
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning to Future Air Traffic Management: Effects of Imperfect Automation on Controller Attention and Performance

Abstract: The further in advance that conflict probe automation predicts a conflict, the greater the uncertainty of prediction; thus, designers should provide users with feedback on the state of the automation or other tools that allow for inspection and analysis of the data underlying the conflict probe algorithm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 18 publications
(32 reference statements)
1
32
1
Order By: Relevance
“…Wickens et al (2009) investigated naturalistic traffic data from en route air traffic control facilities and found that the greater the false alarm rate in a center, the less air traffic controllers tended to respond; however they did not find a relationship between conflict alert rate and less safe separation performance (Wickens et al, 2009). This is in contrast to findings by Rovira & Parasuraman (2010) that found with an imperfect automated conflict probe (supporting the primary task of conflict detection) performance declined with both miss (25% conflicts detected) and false alarm automation (50% conflicts detected). Wickens et al (2009) provides several reasons for not finding operator distrust in automation as a result of excessive and unnecessary alerts including controllers’ perceiving some false alerts as “acceptable” because of conservative algorithms (Lees & Lee, 2007), cultural differences in acceptance among centers, and the relative little evidence for the differences in performance due to types of automation imperfections when the primary task is automated.…”
Section: Domain Experiencecontrasting
confidence: 99%
“…Wickens et al (2009) investigated naturalistic traffic data from en route air traffic control facilities and found that the greater the false alarm rate in a center, the less air traffic controllers tended to respond; however they did not find a relationship between conflict alert rate and less safe separation performance (Wickens et al, 2009). This is in contrast to findings by Rovira & Parasuraman (2010) that found with an imperfect automated conflict probe (supporting the primary task of conflict detection) performance declined with both miss (25% conflicts detected) and false alarm automation (50% conflicts detected). Wickens et al (2009) provides several reasons for not finding operator distrust in automation as a result of excessive and unnecessary alerts including controllers’ perceiving some false alerts as “acceptable” because of conservative algorithms (Lees & Lee, 2007), cultural differences in acceptance among centers, and the relative little evidence for the differences in performance due to types of automation imperfections when the primary task is automated.…”
Section: Domain Experiencecontrasting
confidence: 99%
“…Parasuraman, Sheridan and Wickens (2008) suppose that operators scan the raw information sources less frequently when tasks are delegated to an advanced automation. Rovira and Parasuraman (2010) accordingly assume that in this case ATCOs also exhibit fewer fixations to the radar display compared with manual control, because they invest their freed cognitive resources to focus on secondary tasks. Generally, good monitoring behavior in ATC requires both focused and distributed attention (Moore & Gugerty, 2010).…”
Section: New Roles and Responsibilities For Atcosmentioning
confidence: 99%
“…Licklider (1960) foresaw human-automation interaction as human-machine symbiosis. Advanced human-machine systems exist in areas such as air traffic control (Rovira & Parasuraman, 2010) and managing warehouses (McBride, Rogers, & Fisk, 2011).…”
Section: Introductionmentioning
confidence: 99%